Organpathologie, die den plötzlichen Tod bei Sportlern verursacht: Internationale Untersuchung von Autopsien - Raschka, C.; Parzeller, M.; Kind, M. (Medizinische Klinik, 1999)
BACKGROUND: Accordance of all studies concerning the distribution of causes of cardiovascular sports deaths can only be registered in the dominating role of coronary heart disease and myocardial infarction among athletes > 35 years. In North America a predominance of hypertrophic cardiomyopathy among younger sportsmen (< or = 35 years) is described. This study investigates the conditions in the German speaking countries in central Europe. PATIENTS AND METHODS: The present prospective and retrospective 1.5-year (July 1996 to December 1997) study is based on post-mortem examinations of 28 institutes of pathology and forensic medicine in Germany, Austria and German speaking Switzerland. RESULTS: Twelve out of 113 cases (10.6%) were females, their age being significantly lower (27.8 years, sd = 15.2) than the age of the males (37.5 years, sd = 16.5). Eighty sports deaths (70.8%) were caused by cardiovascular reasons, 33 sports deaths (29.2%) were traumatic in origin. The main cause of cardiovascular deaths of the older athletes (> 35 years) was the coronary heart disease (84.1%). The main reasons for cardiovascular deaths of younger athletes (< or = 35 years) were the coronary heart disease (36.1%) and myocarditis (30.6%). A case of hypertrophic cardiomyopathy was not registered. Most of sports deaths happened in soccer (28), jogging (15), walking (8), cycling (7) and skiing (7). Most of traumatic sports deaths were registered in aerial sports. Four ball players (soccer n = 3, handball n = 1) and 1 motor cyclist suffered from a thrombosis after an orthopedic injury and died due to a consecutive pulmonary embolism. CONCLUSIONS: The distribution of cardiovascular sports deaths displays astonishing regional differences. In contrast to North America anatomical-pathological studies of German speaking countries do not show any dominance of hypertrophic cardiomyopathy among younger athletes, although the pathologists in recent investigations knew the results of Maron. Possible explanations for this phenomenon might be varying selections of patients (top-performance athletes and hobby sportsmen) or a different genetical background.